Employee Performance Determinant Model: Organizational Culture, Career Development and Competence through Employee Loyalty - Arfandy Dinsar; Safrida Safrida; Irawati Nur; Siti Sarah Alyasa Gan (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines the role of employee loyalty in mediating the influence of organizational culture, career development, and competence on employee performance in a public service organization. The research is motivated by inconsistencies in prior findings and the need for an integrated human resource management model within PT. PLN (Persero) South Sulawesi, where performance issues are linked to cultural, developmental, and competency-related challenges. Design/methodology/approach – This research employs a quantitative approach with a correlational design. Data were collected from 92 employees of PT. PLN (Persero) South Sulawesi using purposive sampling. Data analysis was conducted using Structural Equation Modelling (SEM) with AMOS to examine both direct and indirect relationships among variables, including the mediating role of employee loyalty. Finding/Results – The results show that organizational culture, career development, and competence have positive and significant effects on employee loyalty and performance. Employee loyalty also significantly influences performance and acts as a partial mediating variable. The findings indicate that the indirect effects through loyalty strengthen the overall impact of organizational factors on employee performance. Originality/Value – This study offers an integrated structural model that highlights employee loyalty as a key mediating variable in explaining employee performance. The findings emphasize that improving performance requires a holistic approach combining organizational culture, career development, and competence. Practically, this research provides evidence-based recommendations for strengthening human resource management strategies in public sector organizations, particularly in enhancing sustainable employee performance.